Effects of chronic kidney disease on nanomechanics of the endothelial glycocalyx are mediated by the mineralocorticoid receptor - Fels, Benedikt; Beyer, Arne; Cazaña-Pérez, Violeta; Giraldez, Teresa; Navarro-González, Juan F.; Alvarez de la Rosa, Diego; Schaefer, Franz; Bayazit, Aysun K.; Obrycki, Łukasz; Ranchin, Bruno; Holle, Johannes; Querfeld, Uwe; et al. (International journal of molecular sciences, 2022)
Endothelial mechanics control vascular reactivity and are regulated by the mineralocorticoid receptor (MR) and its downstream target, the epithelial Na+ channel (ENaC). Endothelial dysfunction is a hallmark of chronic kidney disease (CKD), but its mechanisms are poorly understood. We hypothesized that CKD disrupts endothelial mechanics in an MR/ENaC-dependent process.
Gesehen am 15.11.2022